HabJariah@Changlun: An Online Donation Platform - Mohd Razmi, Muhammad Aminnur Arif; Packeer Mohamed, Shafinah Farvin; Che Mohamed Arif, Ahmad Suki (Multidisciplinary Applied Research and Innovation, 2023)
The COVID-19 attack in early 2020 shocked the world and led to an announcement by World Health Organization (WHO) as a global pandemic. As a result, numerous sectors, including the economy, business, and tourism, are negatively impacted. Thousands of people had financial hardships, and the White Flags movement gained popularity since many people needed assistance but did not know where to turn. In conjunction to that, HabJariah@Changlun is proposed as a web-based system that will be a central platform for collecting and distributing donations for Changlun residents who are in needs. Additionally, it serves as a platform for sellers to advertise and sell their goods. The primary goal of this system is to provide an efficient, systematic, and trustworthy approach of donating, receiving donation and selling products. The Rapid Application Development (RAD) methodology was used to implement this project, which consists of four phases, starting with requirements planning, continued with user design, construction, and ended with cutover. This project will be beneficial for the Changlun residents, especially the donor, the people in need, and the seller in Changlun. The donor now will have a trustworthy platform to donate their money. Furthermore, the people in need will receive the benefits as they have a platform to seek for help. On the other hand, the sellers can have a platform to sell their products. Most importantly, the less fortunate people can be helped.